Temperate Bacteriophage Infectious for Asporogenic Variants of Bacillus pumilus - Bramucci, Michael G. (1974)
Bacillus pumilus strain NRRL B-3275 is lysogenic for an inducible, nondefective temperate bacteriophage φ75. φ75 infects and lysogenizes several asporogenic mutants of B. pumilus strain NRS 576 but does not productively infect the spore(+) parent. φ75 DNA is a linear duplex with a mol wt of about 29 × 10(6) and a buoyant density of 1.701 g/cm(3). The location of the φ75 prophage attachment site on the chromosome of both host strains is adjacent to a lysine marker. The apparent order is φ75 att lys trp.